Compliance with stylistic standarts in teacher speech - Rakhimova , Saida; Bahriddinova , Kumush (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
This article examines the role of a teacher’s speech in pedagogical activity, its stylistic formation, and the issues of adherence to speech norms. The article analyzes the fundamental requirements for a teacher’s speech: clarity, logic, richness, and, most importantly, the stylistic differentiation of speech according to the situation. Furthermore, the pedagogical and psychological significance of speech culture in shaping the worldview of students and pupils is highlighted.